2007
DOI: 10.15666/aeer/0501_043056
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Biomass in Semi-Arid Communal Sandy Rangelands in the Western Bophirima District, South Africa

Abstract: Abstract. Soil microbial biomass is considered as an important early indicator of changes that may occur in the long term with regard to soil fertility and constitutes an important source and sink of nutrients. In South Africa, rangeland monitoring has mostly focused on assessing changes of aboveground vegetation in response to land uses effects, but the associated changes at belowground soil level remain a topic of further research. The aim of this study was to explore soil microbial biomass at three sites un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Range rehabilitation promotes litter and organic matter supply by reducing soil disturbance, restoring herbaceous vegetation and increasing biomass production (Verdoodt et al, 2010;Mekuria and Aynekulu, 2011). Holt (1997) and Raiesi and Asadi (2006) reported a reduction in C mic under long-term grazing compared to adjacent ungrazed sites in Australia and Iran, respectively, whereas Moussa et al (2007) found non-significant differences in C mic between grazed and ungrazed plots in the semi-arid rangeland of South Africa. The microbial biomasses recorded in the restored rangeland in the Njemps Flats (73 to 156 µg/g soil) are relatively low compared to the literature data for the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…Range rehabilitation promotes litter and organic matter supply by reducing soil disturbance, restoring herbaceous vegetation and increasing biomass production (Verdoodt et al, 2010;Mekuria and Aynekulu, 2011). Holt (1997) and Raiesi and Asadi (2006) reported a reduction in C mic under long-term grazing compared to adjacent ungrazed sites in Australia and Iran, respectively, whereas Moussa et al (2007) found non-significant differences in C mic between grazed and ungrazed plots in the semi-arid rangeland of South Africa. The microbial biomasses recorded in the restored rangeland in the Njemps Flats (73 to 156 µg/g soil) are relatively low compared to the literature data for the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…Because grazing may be beneficial for vegetation production and C allocation to soils, it has also been found that exclosure of livestock does not benefit grassland soil C sequestration in some semi-arid rangeland (Nosetto et al 2006;Shresta & Stahl 2008) and savanna contexts (Moussa et al 2007). Enclosure of grasslands from livestock grazing may also restrict the access of livestock keepers to functional grazing lands, adversely affect herders' incomes and displace grazing intensity onto unenclosed lands (Williams 1996).…”
Section: Sequestration Potential Of Specific Management Practicesmentioning
confidence: 99%
“…It also acts as biological early indicator of changes [22,23]. It makes up 1-5% of total SOC [24] and acts as the most active component in the biochemical process of SOC turnover [25].…”
Section: Introductionmentioning
confidence: 99%